Membangun Nagari Talang Anau melalui Penguatan Kapasitas Aparatur Pemerintahan Nagari - Roni Ekha Putera; Tengku Rika Valentina; Rifki Dermawan (Warta Pengabdian Andalas, 2021)
Governance has become an interesting field of study in public administration. The shifting of authority from central government to local government and even to village level becomes a challenge as well as an opportunity for bureaucrats to provide community services. It justifies why understanding of ideal and relevant governance is needed to solve current problems. As a bureaucracy aiming to serve the community, Nagari is expected to be able fulfilling the society’s needs. Based on this condition, this initiative was conducted in Nagari Talang Anau, Kecamatan Gunuang Omeh, 50 Kota Regency, West Sumatera Province to solve the problems of limited understanding of local government employees regarding state administration (government). To achieve this goal, the program began by contacting and making confirmation with Wali Nagari and then followed by training and socialization regarding state administration system (government), public policy formulation in Nagari, and community services. The result indicated that there were several problems in Nagari Talang Anau administration, such as limited access to information and technology sector, lack of programs by Lembaga Pemberdayaan Masyarakat (LPM) and insufficient human resources. Based on these problems, the authors and the team members suggested that Nagari administration should focus more on the issue of improving the quality of human resources.